2014
DOI: 10.1007/s11695-014-1319-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbohydrate Restriction in Patients with Hyperinsulinemic Hypoglycemia after Roux-en-Y Gastric Bypass

Abstract: A 30-g carb-restricted meal may help to prevent post-prandial hypoglycemia in patients with post-RYGB hypoglycemia. The use of a liquid, low GI, supplement offers no additional advantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 20 publications
1
18
0
5
Order By: Relevance
“…This suggests that data interpretation should take into account -The physiological condition that allows a postprandial hyperglycemic peak to be expressed, which does not occur in all patients, and which is related to a mechanism other than meal composition -The carbohydrate content of the meal which modifies the maximum IG in patients who are likely to present this type of abnormality [19, 20, this study] -A high glycemic index of the meals may increase the height of the peak. Botros et al had shown that a very low glycemic index diet can reduce plasma glucose [18]. The glycemic load, which is a combined assessment of the carbohydrate content and of the glycemic index, proved to be a determinant for the maximum IG in this study.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This suggests that data interpretation should take into account -The physiological condition that allows a postprandial hyperglycemic peak to be expressed, which does not occur in all patients, and which is related to a mechanism other than meal composition -The carbohydrate content of the meal which modifies the maximum IG in patients who are likely to present this type of abnormality [19, 20, this study] -A high glycemic index of the meals may increase the height of the peak. Botros et al had shown that a very low glycemic index diet can reduce plasma glucose [18]. The glycemic load, which is a combined assessment of the carbohydrate content and of the glycemic index, proved to be a determinant for the maximum IG in this study.…”
Section: Discussionsupporting
confidence: 58%
“…The increase in glucose (140-160 mg/dl at 45 min) was similar after ingestion of 25 or 50 g of glucose solution or after a test meal that included 37.5 g of glucose, lipids, and proteins. Botros et al [18] compared two meals that included the same quantity of carbohydrates (28 or 30 g) with proteins and lipids, but one contained carbohydrates with an extremely low glycemic index. This study involved 14 patients with hyperinsulinemic hypoglycemia around 2 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this degree of carbohydrate restriction makes compliance challenging and may not be optimal for the long-term, few studies address the optimal quantity of carbohydrates. In one study, limiting a test meal to 30 grams of solid carbohydrate or 28 grams of liquid low glycemic index supplement was successful in preventing hypoglycemia in patients with PBH [17]. A third study in 10 patients with PBH evaluated the relative carbohydrate composition of a test meal; a high carbohydrate meal containing mostly sucrose provoked postprandial hypoglycemia, while an isocaloric high-carbohydrate meal composed of fructose was associated with lower glycemic peak, lower insulin secretion, and no induction of hypoglycemia [18].…”
Section: Prevention Of Hypoglycemia In Post-bariatric Patientsmentioning
confidence: 99%
“…Therefore, the mainstay treatment is to avoid initial hyperglycaemia postprandial by restricting carbohydrate intake and avoiding a high glycaemic index diet and simple sugars. Most patients respond very well to the very low or low carbohydrate diet in conjunction with high protein intake . Dietary modifications include splitting meals into smaller, more frequent meals (5–6 per day); also, it is recommended to delay any liquid intake until at least 30 min afterwards and in some cases, lying down for 30 min after a meal alleviates symptoms.…”
Section: Treatment Optionsmentioning
confidence: 99%